Penerapan Multi Factor Evaluation Process Dalam Penerimaan Asisten Dosen Pada STMIK Triguna Dharma - Ramadhan, Puji Sari (STMIK Budi Darma, 2019)
In helping the role of a lecturer in carrying out learning as well as an effort in improving the quality of learning it is necessary to appoint a Lecturer Assistant who is also in charge of replacing the role of the lecturer who is unable to attend. In the acceptance process of the Lecturer Assistant, it is necessary to use objective and accurate criteria and assessment using the calculation method to have a universal concept in the science of Decision Support Systems. For this reason, it is necessary to build a scoring system that can later produce decisions in selecting prospective Lecturer Assistants. Based on these views, the acceptance of the Lecturer Assistant will use one method in the Decision Support System that can produce a decision based on the ranking or ranking of each alternative, namely the Multi-Factor Evaluation Process method. With the application of this method that will be applied in an application, the system can help the institution in determining the feasibility of the acceptance process of the Lecturer Assistant so that later the Lecturer Assistant will be chosen based on the ranking of values that have been generated through the Multi-Factor Evaluation Process.